Juridical Review Of The Enforcement Of Criminal Laws For Illegal Tobacco Trafficers Without Excise Reviewed From Legislationconcerning Excise - Reimanda Zepanta Ginting; Andry Syafrizal Tanjung; M. Hary Angga Pratama Sinaga (CV. AFDIFAL MAJU BERKAH, 2024)
The case of the circulation of illegal goods, especially cigarettes without duty in Tanjung Balai City, is a case that is attracting serious attention, because there were a lot of catches by Teluk Nibung Customs and Excise officers during the 2021 to 2022 period, in the form of 2,313,172 cigarettes. With a total value of goods of Rp. 9,840,000,000.00 (nine billion eight hundred and forty million rupiah) with a total potential state loss of Rp. 3,913,000,000.00 (three billion nine hundred and thirteen million rupiah). This research aims to determine the factors causing the circulation of illegal cigarettes without duty in Tanjung Balai, law enforcement against the circulation of illegal cigarettes without duty in Tanjung Balai, as well as obstacles and efforts to enforce the law on the distribution of illegal cigarettes without duty.The nature of research in writing a thesis uses descriptive analysis, the type of research uses Normative law while the data collection method uses Library Research, and the type of data in this research uses Secondary Data. Criminal acts regarding fake excise stamps and the use of used BKC excise stamps are regulated in Article 55 of Law no. 39 of 2007 and factors that can hinder the Directorate General of Customs and Excise and related agencies from effectively monitoring and enforcing the law on the distribution of illegal tobacco in the city of Medan are the lack of public awareness of illegal tobacco, weak supervision and enforcement carried out by the relevant authorities. , there is still a lack of awareness of Tobacco producers in producing illegal Tobacco. The government is expected to increase State revenues from the excise sector along with efforts to safeguard State revenues and issue several strategic policies, namely by neutralizing the market for Illegal Tobacco products.